Edukasi Siswa SMPN 3 Samboja Tentang Penggunaan Obat Yang Baik Dan Benar Melalui Kegiatan DAGUSIBU - Mus, Nurul Muhlisa (Fakultas Kehutanan dan Lingkungan Tropis, Universitas Mulawarman, 2023)
The high efforts of self-medication by the community can pose a risk of drug use errors and irrational therapy if they are not equipped with adequate knowledge. There needs to be an understanding of how to get the right and proper medicine, an understanding of the right and proper way to use medicine, an understanding of how to store medicine properly and correctly and an understanding of how to dispose of medicine properly and correctly. the educational method uses the lecture method with power point media and demonstration tools in the form of posters to educate the use of drugs that are good and right. The method carried out in several stages includes: pre-test, delivery of service material, discussion and question and answer, ending with a post-test. The purpose of this community service is that students are able to understand the proper and correct use of drugs from an early age. In addition, it is also expected to be able to help increase awareness of the use of drugs that are good and right in the family. From the results of the pre and post-tests, it can be seen that there has been an increase in the target's understanding (students of SMPN 3 Samboja) regarding the correct and proper use of drugs.